3. The effects of KEM CON ONG and KEM TRI BONG creams on thermal burn in rats - Anh, Pham Thi Van; Minh, Tong Cong; Loan, Nguyen Thi Thanh; Ngan, Nguyen Thi; Truong, Ngo Viet; Giang, Nguyen Kim; Nga, Nguyen Thi Quynh; Tung, Tran Thanh (Tạp chí Nghiên cứu Y học, 2023)
The present study evaluated the healing effect of topical administration of KEM CON ONG and KEM TRI BONG creams on thermal burns in rats, and their systemic toxicity in burned rats. Thermal burns were induced on the dorsal region of rats using a standard burning technique. The burned areas were covered topically with silver sulfadiazine, KEM CON ONG, or KEM TRI BONG twice a day for 21 days. The results indicated that treatment with KEM CON ONG and KEM TRI BONG significantly reduced the size of the wounded area, increased the hydroxyproline content in animals’ skin tissues, and improved the histopathological structure of skin tissues. KEM TRI BONG exerted better effects than KEM CON ONG on thermal burns in rats. Besides, our study demonstrated that topical administration of KEM CON ONG and KEM TRI BONG creams caused no significant change in the general status, haematological parameters, renal and hepatic functions. Additionally, they did not alter the histology of liver and kidney in animals. In conclusion, the topical application of KEM CON ONG and KEM TRI BONG creams exerted healing effects on the burned skin, and did not cause systemic toxicity in a rat model.